Fermi-level equilibrium-driven trap filling in multibandgap PbS quantum dot solids enabling record voltage generation and improved carrier transport in high-performance solar cells - Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup Kumar (ACS Energy Letters, 2025)
To leverage the unique optical properties of quantum dots (QDs) in solar cells, it is crucial to address electronic traps from unsaturated surface states of high surface area QDs. Despite advancements in surface passivation, even the best-coupled QD solids exhibit significant sub-bandgap trap states. This study introduces engineered multibandgap PbS QD solids that achieve passivation of deep traps below the conduction band through electron migration from dopant QDs. Our findings indicate that electron flow, driven by Fermi energy balancing in blend films, fills deep trap states, reducing trap density by half and shifting trap energy positions closer to the conduction band. During electrical transport, trap filling minimizes trapping and detrapping events, enhancing overall carrier mobility, despite higher-bandgap dopant QDs not contributing to carrier transport due to their unfavorable energy positions. Improved trap passivation in coupled QD solids leads to a record V oc of 725 +/- 10 meV for the 1.33 eV excitonic peak of QDs and a power conversion efficiency exceeding 14% in solar cells.

Synergistic improvement of narrow bandgap PbS quantum dot solar cells through surface ligand engineering, near-infrared spectral matching, and enhanced electrode transparency - Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2025)
The tunability of the energy bandgap in the near-infrared (NIR) range uniquely positions colloidal lead sulfide (PbS) quantum dots (QDs) as a versatile material to enhance the performance of existing perovskite and silicon solar cells in tandem architectures. The desired narrow bandgap (NBG) PbS QDs exhibit polar (111) and nonpolar (100) terminal facets, making effective surface passivation through ligand engineering highly challenging. Despite recent breakthroughs in surface ligand engineering, NBG PbS QDs suffer from uncontrolled agglomeration in solid films, leading to increased energy disorder and trap formation. The limited NIR transparency of commonly used indium-doped tin oxide (ITO) electrodes and inadequate NIR radiation from commercially available solar simulators further compromise the true performance of NBG PbS QDs in solar cells. Here, we employ a hybrid ligand strategy based on inorganic cadmium halide and organic thiol molecules, leading to the partial substitution of surface Pb atoms with Cd heteroatoms. This hybrid ligand strategy substantially reduces undesired QD fusion in solid films, improving the photophysical and electronic properties. By modulating the thickness of the ITO layer and managing refraction loss through a ZnO layer coating, we improved NIR transparency to above 80%. We combine an NIR light source with a solar simulator to achieve near-ideal spectral matching for a broader range with standard AM1.5G illumination. Enhancements in surface passivation of QDs, improvements in NIR transparency of electrodes, and a spectral matched light source setup help us achieve solar cell power conversion efficiencies of 12.4%, 4.48%, and 1.37% under AM 1.5G, perovskite filter, and silicon filter illuminations, respectively. A record open-circuit voltage (V oc) of 0.54 V and short-circuit current density (J sc) of 38.5 mA/cm2 are achieved under AM 1.5G illumination. We attribute these advancements in photovoltaic parameters to the reduction in Urbach tail states and intermediate trap density originating from superior surface passivation of QDs.
Keywords: lead sulfide; ligand passivation; near-infrared; quantum dots; solar cell; tandem solarcell